2016
DOI: 10.2147/ijn.s94270
|View full text |Cite
|
Sign up to set email alerts
|

Controlled-release of tetracycline and lovastatin by poly(D,L-lactide-co-glycolide acid)-chitosan nanoparticles enhances periodontal regeneration in dogs

Abstract: Chronic periodontitis is characterized by inflammation of periodontal tissues, leading to bone resorption and tooth loss. The goal of treatment is to regenerate periodontal tissues including bone and cementum lost as a consequence of disease. The local delivery of tetracycline was proven to be effective in controlling localized periodontal infection without apparent side effects. Previous studies suggested that lovastatin has a significant role in new bone formation; however, the local delivery of lovastatin m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…The biomaterial scaffold as the cell carrier and exogenous graft should have a positive effect or no palpable side effect on cell growth and differentiation, and it should be accompanied by good biocompatibility and easy degradation in vivo after implantation [ 11 , 12 ]. PLGA has been served as a drug carrier because of its biocompatibility and biodegradation [ 13 , 14 ]. Seed cells derived from autologous tissue used to construct engineered tissue are the preferable choice.…”
Section: Discussionmentioning
confidence: 99%
“…The biomaterial scaffold as the cell carrier and exogenous graft should have a positive effect or no palpable side effect on cell growth and differentiation, and it should be accompanied by good biocompatibility and easy degradation in vivo after implantation [ 11 , 12 ]. PLGA has been served as a drug carrier because of its biocompatibility and biodegradation [ 13 , 14 ]. Seed cells derived from autologous tissue used to construct engineered tissue are the preferable choice.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting nanofibres have the potential to be incorporated into PMMA based resin to produce denture materials. Another biopolymer chitosan, has also been reported as a nanocarrier for antibacterial compounds for application in dental diseases (B. S. Lee et al, 2016).…”
Section: Polymeric Nanomaterialsmentioning
confidence: 99%
“…Despite pioneering studies, the possibility of using MPDA nanoparticles loaded with tetracycline hydrochloride (TH) and wrapped with GO as a drug carrier has not yet been demonstrated to the best of our knowledge. TH is used as the model drug in this work because it is a well-known broad-spectrum antibiotic with low toxicity and its local delivery is known to be effective in the control of bacterial infections …”
Section: Introductionmentioning
confidence: 99%
“…TH is used as the model drug in this work because it is a well-known broad-spectrum antibiotic with low toxicity and its local delivery is known to be effective in the control of bacterial infections. 16 GO, the two-dimensional layer of sp 2 -bonded carbon, with rich functional groups on its surface, including epoxy, hydroxyl, and carboxyl groups, has received tremendous attention in the field of materials. 17,18 In 2008, Dai et al first reported that GO can be used as an efficient nanocarrier for drug delivery.…”
Section: Introductionmentioning
confidence: 99%